Highly‐Tunable Nickel Cobalt Oxide as a Low‐Temperature P‐Type Contact in Organic Photovoltaic Devices. Issue 4 (26th November 2012) - Ndione, Paul F.; Garcia, Andres; Widjonarko, N. Edwin; Sigdel, Ajaya K.; Steirer, K. Xerxes; Olson, Dana C.; Parilla, Philip A.; Ginley, David S.; Armstong, Neal R.; Richards, Robin E.; Ratcliff, Erin L.; Berry, Joseph J.
Abstract We report on the investigation of nickel cobalt oxide (NixCo3−xO4) thin films grown by pulsed laser deposition as hole‐transport interlayers (HTL) in organic photovoltaic (OPV) devices. Films of 7 nm thickness were grown under various oxygen deposition pressures (pO2) in the range of 2–200 mTorr. We explore both bulk and surface properties of these thin films. The workfunction (ϕ) for each of the films was statistically similar (∼4.7 eV), regardless of pO2. There was not a strong dependence of the power conversion efficiency (η) on the conductivities of the HTLs varying between 0.009 ‐ 10 S/cm. The observed differences in OPV efficiencies (ranging from 1.16 to 2.46%) were correlated to the near surface chemical composition of the NixCo3−xO4 HTL, as observed by differences in the relative surface hydroxyl concentration. The critical role of the near‐surface composition of the HTL at the HTL/organic interface was further explored by modifying the hydroxyl concentration using an oxygen plasma treatment. This treatment mitigated the impact of surface hydroxyl coverage, demonstrating either identical or increased values for ϕ and η, regardless of initial pO2 in the creation of the NixCo3−xO4 HTL. To further explore this we also employed a phosphonic acid surface modification agent on the HTL, increasing ϕ to 5.2 eV producing the best η value of 3.4%, equivalent to the PEDOT:PSS control devices. These results indicate that nickel cobalt oxide is a promising p‐type oxide for carrier‐selective interlayers in organic solar cells; however, for this to be fully realized the specific surface chemistry at the oxide/polymer interface must be controlled to increase ϕ and optimize device performance.